Drug nanocrystals: A way toward scale-up - Raghava Srivalli K.M.; Mishra B. (My University, 2025)
Drug nanocrystals comprise unique drug delivery platforms playing a significantly important and distinctive role in drug delivery and as such, the industry and academia are spending a lot of their time and money in developing the nanocrystal products. The current research works in this field depict a vivid shift from lab scale optimization studies to scale up focused studies. In this emerging scenario of nanocrystal technology, a review on some exemplary and progressing research studies with either scalability as their objective or upscaling as their future scope may smoothen the future upscaling attempts in this field. Hence, this paper reviews the efforts of such research works as case studies since an analysis of such research studies may input certain beneficial knowledge to carry out more scale up based research works on nanocrystals. © 2014 King Saud University